(3GdaUjM aj GddZIs - (3CMeO Hf jMji Hf RjO Hf SjGQ GdTjHGfqj HGdhdGA, CHh GdYHGS, GdeYQha HKYdH,J (B291 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3gPG cJGH GNJjGQ aUjM GdcdGe eeG jLQi ai cdGe GdfGS hcJHge aefg eG ajg dZI hGMOI HGH aYdJ HaJM GdYjf s
(3BNQgG (B:s
(3hbGd GHf GdCYQGHi hjbGd dLdO HjVI GdEfSGf GdUaf hjbGd dg ef PhGJ GdNa Je GdcJGH hGdMeO ddg s
(3YdjgG bQGAJGf HChdgG SfI (B682(3g` hHBNQgG SfI (B711(3g` hGdfSNI ebGHdIs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B252s
Keywords: (3GddZIs